Homer: what culture? What society? - Zanon, Camila Aline (Romanitas - Revista de Estudos Grecolatinos, 2013)
From the archaeological researches made by Heinrich Schliemann in the end of the 19th century, a new past was framed to the Homeric epics. Previously considered having a mythological content, after the archaeological discoveries that culminated in the definition of a Bronze Age, they started to be viewed as a source for that age. However, those same archaeological researches and other ones also revealed the inconsistencies of the Homeric epics relating to such an age and its proximity to the Iron Age. The present paper aims to discuss those discoveries, running through with the reader the ways that conducted the epics from just a figment of poetic imagination to its role as historical source and mainly to enquire about which society and which culture those poems refer to.
Keywords: Homer; Iliad; Archaeology; Bronze Age; Iron Age